2019
DOI: 10.1097/tp.0000000000002635
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aortoiliac Stenosis on Graft and Patient Survival in Kidney Transplant Recipients Using the TASC II Classification

Abstract: Background. Patients with end-stage renal disease and aortoiliac stenosis are often considered ineligible for kidney transplantation, although kidney transplantation has been acknowledged as the best therapy for end-stage renal disease. The clinical outcomes of kidney transplantation in patients with aortoiliac stenosis are not well-studied. This study aimed to assess the impact of aortoiliac stenosis on graft and patient survival. Methods. This retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 40 publications
2
20
1
Order By: Relevance
“…The pooled RR showed no significant higher risk of graft failure in KTR with VC ( n = 212; RR: 3.41; 95% CI 0.97–11.96; P = 0.05) . Rijkse et al also found a significant graft survival difference between KTR with a TASC II C/D lesion in comparison to KTR without any TASC II lesions (5‐year graft survival: no TASC II lesions: 60%, TASC II C/D lesion: 22%, log‐rank test: P < 0.001).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The pooled RR showed no significant higher risk of graft failure in KTR with VC ( n = 212; RR: 3.41; 95% CI 0.97–11.96; P = 0.05) . Rijkse et al also found a significant graft survival difference between KTR with a TASC II C/D lesion in comparison to KTR without any TASC II lesions (5‐year graft survival: no TASC II lesions: 60%, TASC II C/D lesion: 22%, log‐rank test: P < 0.001).…”
Section: Resultsmentioning
confidence: 95%
“…They found a statistical significant difference with an incidence of 6.5% in KTR without VC and 21.7% in KTR with any VC ( P = 0.035) . Rijkse et al found that, among deceased patients, death from a cardiovascular cause was more frequent in patients with any TASC II lesion (any TASC II lesion: 35.4%, no TASC II lesion 19.1%, P = 0.035) .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations